Hemogregarine Diversity Infecting Brazilian Turtles with a Description of Six New Species of Haemogregarina (Apicomplexa: Adeleorina: Haemogregarinidae) - Úngari, Letícia Pereira [UNESP]; Santos, André Luiz Quagliatto; da Silva, Reinaldo José [UNESP]; O’Dwyer, Lucia Helena [UNESP] (MDPI, 2023)
(1) Background: Hemoparasites of the genus Haemogregarina (Haemogregarinidae) are commonly reported in freshwater turtles. However, in Brazil, only three species have currently been characterised using molecular methods. This study aimed to bring new insights on the diversity of species of Haemogregarina infecting Brazilian freshwater turtles from Mato Grosso and Goiás states using molecular and morphological tools. (2) Methods: In total, 2 mL of blood was collected, with between two to five blood smears prepared, fixed with absolute methanol, and stained with a 10% Giemsa solution. Blood was stored at −20 °C for molecular analysis targeting the 18S rRNA gene. Fragments of the organs (liver, spleen, heart, and kidney) were separated and stained with hematoxylin-eosin. (3) Results: A total of 40 turtles were screened and hemogregarines were observed in 34 (85%) individuals (3 Podocnemis expansa and 31 Podocnemis unifilis). Haemogregarina embaubali and six new species of Haemogregarina were observed and formally described as follows: H. unifila n. sp., H. rubra n. sp., H. goianensis n. sp., H. araguaiensis n. sp., H. tigrina n. sp., and H. brasiliana n. sp. (4) Conclusions: This study contributes to the diversity and knowledge of Brazilian fresh-water turtle blood parasites, using integrative approaches for diagnosing and characterizing hemoparasites, with the identification of six undescribed species.
Keywords: Brazil; diversity; fresh-water turtles; Hemoparasite; PCR; taxonomy